Validation of whole blood impedance aggregometry as a new diagnostic tool for HIT - Morel-Kopp, Marie-Christine; Tan, Chee Wee; Brighton, Timothy A; McRae, Simon; Baker, Ross; Tran, Huyen; Mollee, Peter; Kershaw, Geoffrey; Joseph, Joanne; Ward, Christopher; the ASTH Clinical Trials Group; on behalf of (Thrombosis and Haemostasis, 2012)
Heparin-induced thrombocytopenia (HIT) remains a challenge, with diagnosis confirmed only by functional assays. The gold standard 14C-se-rotonin release assay (SRA) is highly sensitive but technically challenging and unsuitable for routine use. We conducted a large study to validate whole blood impedance aggregometry (WBIA) as a suitable diagnostic tool for HIT. WBIA and SRA were used to test 181 samples positive for H-PF4 antibodies by PaGIA or ELISA. Using the same high responder donor, 77 samples were positive by WBIA (aggregation with low-dose but not high-dose heparin). Using the strict definition for SRA positivity, 72 samples were true HIT. In nine samples, serotonin release with high-dose heparin dropped by > 50% but was still >20%; these were retested after a one-half dilution and 8/9 became positive. Ten other samples were discrepant between the two assays: one strongly positive (89% release) and six weakly positive samples by SRA (average release 56%) were WBIA negative. When these samples were retested using a random donor, only two remained SRA positive. Three samples were strongly WBIA positive but SRA negative; two were retested by SRA with 0.5IU/ml heparin and one became positive. Under controlled conditions, using the same selected high-responder donor, WBIA and SRA performed similarly with slightly increased sensitivity of the WBIA when using the strict definition of SRA positivity. WBIA is easy to perform with rapid turn-around time and warrants a multi-laboratory trial to complete its validation as a confirmatory assay for platelet-activating HIT antibodies.
Keywords: Heparin; heparin-induced thrombocytopenia; 4T′s score; serotonin release assay; whole blood impedance aggregometry